Розвиток кримінального законодавства, що передбачає відповідальність за службове підроблення: історико-правовий аналіз (I століття до н. е. – початок XX століття) - Остапенко, Я. С.; Ostapenko, Ya. S. (Вісник Кримінологічної асоціації України. - 2015. - № 3 (11). - С. 199-208., 2015)
Розглянуто розвиток кримінального законодавства, що передбачає відповідальність за службове підроблення, проведено історично-правовий аналіз виникнення та формування поняття «службове підроблення» та відповідальності за його вчинення в історично-правових документах від зародження римського права до Жовтневих подій 1917 року, вивчено досягнення історичних епох і процес адаптації поняття «службове підроблення» до сучасних правових реалій.

One of the crime varieties in the field of service activities is forgery, which has come a long historical path up to consolidation in a modern legal norm in domestic and foreign legislations. A prerequisite for the emergence of such a specific phenomena as forgery served various factors: the collapse of primitive society, the emergence of private property; introduction of writing, development of legal turnover; emergence of money and monetary development; decline in subsistence farming, the development of commodity and money relations, etc. All these factors since their appearance at some stage of social development created the need to prohibit socially dangerous fakes that were a prototype of the forgery. The issues of historical development of forgery at various times were the interest of many foreign and domestic scientists; especially we should note the following: T. B. Basov, N. O. Hutorova, V. I. Dinek, A. I. Dolhov, O. O. Dudorov, O. O. Zhyzhylenko, B. V. Zdravomyslov, S. M. Inshakov, M. I. Fialka and many others. The objective of this research is the need to follow the historical development of forgery in written monuments of history from ancient times to the Great October Revolution of 1917, and to analyze the achievements of those eras and to adapt them to modern legal realities. The development of criminal and legal liability for forgery in historical and legal aspect is analyzed in this research. Analyzing the first rudiments of forgery in Roman law, its form and consolidation, it is possible to conduct a comparative analysis of the concept of forgery in canonical law, namely in the Papal Decretals. The following historical development the forgery got in the national legislation, namely the Russian Truth. A kind of prototype of the forgery at that time was slander and forgery of near-boundary marks. Besides, a detailed analysis of criminal liability’s consolidation for forgery subjected to such historical monuments as Pskov Charter, Lithuanian Statutes, Ivan the Terrible Code of Law, Catholic Code, Military Clauses, “Rights, which are the Basis for Litigation of the People of Malorossiia», Code of Criminal and Correctional Punishments and Criminal Code of 1903. The author of the article concludes that the historical analysis of the legislation that has regulated forgery, allows us to trace the main ways of legal thought’s development on this issue. Studies of foreign and domestic scholars as well as accumulated knowledge in the past are an integral part and a guide for modern scientific research of this problem. Extensive experience of legal sciences is a rich ground for the development of ideas and approaches to solve the issue of differentiation and expansion of the concept of forgery.

Рассмотрено развитие уголовного законодательства, предусматривающего ответственность за служебный подлог, проведен исторически-правовой анализ развития и формирования понятия «служебный подлог» и ответственности за его совершение в исторически-правовых документах от зарождения римского права до Октябрьской революции 1917 года, изучены достижения исторических эпох и способы адаптации понятия «служебный подлог» к современным правовым реалиям.
Остапенко, Я. С. Розвиток кримінального законодавства, що передбачає відповідальність за службове підроблення: історико-правовий аналіз (I століття до н. е. – початок XX століття) // Вісник Кримінологічної асоціації України. - 2015. - № 3 (11). - С. 199-208.
Остапенко Я. С. "Розвиток кримінального законодавства, що передбачає відповідальність за службове підроблення: історико-правовий аналіз (I століття до н. е. – початок XX століття)." Вісник Кримінологічної асоціації України 3 (2015): 199-208.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; службове підроблення; римське право; канонічне право; Руська правда; Псковська судна грамота; Литовські статути; Судебник Івана Грозного; Соборне Укладення; Права, за якими судиться малоросійський народ; Укладення про покарання кримінальні та виправні; Кримінальне укладення 1903 року; forgery; Roman law; canonical law; Russian Truth; Pskov Charter; Lithuanian Statutes; Ivan the Terrible Code of Law; Catholic Code; Rights, which are the Basis for Litigation of the People of Malorossiia; Code of Criminal and Correctional Punishments; Criminal Code of 1903; служебный подлог; римское право; каноническое право; Русская правда; Псковская судная грамота; Литовские статуты; Судебник Ивана Грозного; Соборное Уложение; Права, по которым судится малороссийский народ; Уложение о наказаниях уголовных и исправительных; Уголовное уложение 1903 года; Україна. Ukraine. Украина